Flow Cytometry in the Detection of Abnormal Cells and Cell Debris Based on the Expression of Cellular Markers (Razi Medical Journal, 2025)
Flow cytometry is a fundamental technique that is used in the fields of cancer biology and immunology to distinguish among the types of cells in mixed populations.  As a diagnostic tool, it is also used by clinicians to identify abnormal cell populations associated with diverse diseases. The abnormal cell populations are identified through the specific binding of the antibodies to the marker of interest.  Fluorescence measurements provide quantitative and qualitative data about cell surface receptors or intracellular molecules. The study examined the expression of CD49b, CD49c, and CD326 in the human colon cancer-derived cell line COLO 320 using immunofluorescence staining and flow cytometry. The cells were incubated with FITC-conjugated monoclonal antibodies and an isotype control, obtained from Serotec. Data were analyzed with the Cell Quest software. The FSC/SSC plot for the COLO 320 cancer cell line reveals two populations of cells with varying sizes and heterogeneity. Histograms show the expression of CD49b and CD49c, with moderate positivity for anti-CD49b and no specificity for anti-CD49c. CD326 staining in COLO 320 cells has two peaks due to subpopulations of varying degrees of commitment and origin. The CD326-positive population is gated, and unspecific binding is ruled out by the negative control.
Keywords: Flow Cytometry, Cancer, Immunofluorescence.